BSN-mesh and its basic parallel algorithms. (2015) - Wei, Wenhong; Li, Qingxia; Tao, Ming
Mesh is the most famous, common and effective interconnection network, which has become the preferred topology of parallel processing and parallel computing systems. At the same time the Biswapped Network (BSN) provides an efficient two-level structure for large scalable, inheritance, modular architecture. In this paper, we present BSN-mesh as two-tier architecture with the advantages of both BSN and mesh. On the basis of the presented BSN-mesh, topological structure and many basic algorithms such as broadcast, data sum, prefix sum, packet routing and sorting are investigated. Compared with other two-tier architectures, especially OTIS-mesh, the time complexities of the mentioned algorithms running on BSN-mesh are much lower and BSN-mesh is more competitive.